High burden of genetic conditions diagnosed in a cardiac neurodevelopmental clinic. (19th September 2016) - Goldenberg, Paula C.; Adler, Betsy J.; Parrott, Ashley; Anixt, Julia; Mason, Karen; Phillips, Jannel; Cooper, David S.; Ware, Stephanie M.; Marino, Bradley S.
Abstract: Background: There is a known high prevalence of genetic and clinical syndrome diagnoses in the paediatric cardiac population. These disorders often have multisystem effects, which may have an important impact on neurodevelopmental outcomes. Taken together, these facts suggest that patients and families may benefit from consultation by genetic specialists in a cardiac neurodevelopmental clinic. Objective: This study assessed the burden of genetic disorders and utility of genetics evaluation in a cardiac neurodevelopmental clinic. Methods: A retrospective chart review was conducted of patients evaluated in a cardiac neurodevelopmental clinic from 6 December, 2011 to 16 April, 2013. All patients were seen by a cardiovascular geneticist with genetic counselling support. Results: A total of 214 patients were included in this study; 64 of these patients had a pre-existing genetic or syndromic diagnosis. Following genetics evaluation, an additional 19 were given a new clinical or laboratory-confirmed genetic diagnosis including environmental such as teratogenic exposures, malformation associations, chromosomal disorders, and single-gene disorders. Genetic testing was recommended for 112 patients; radiological imaging to screen for congenital anomalies for 17 patients; subspecialist medical referrals for 73 patients; and non-genetic clinical laboratory testing for 14 patients. Syndrome-specific guidelines were available and followed for 25 patients with known diagnosis. American Academy of Pediatrics Red Book asplenia guideline recommendations were given for five heterotaxy patients, and family-based cardiac screening was recommended for 23 families affected by left ventricular outflow tract obstruction. Conclusion: Genetics involvement in a cardiac neurodevelopmental clinic is helpful in identifying new unifying diagnoses and providing syndrome-specific care, which may impact the patient's overall health status and neurodevelopmental outcome.